Dynamics of the association between dung beetles (Coleoptera: Scarabaeidae) and the dog parasite Spirocerca lupi (Nematoda: Spiruromorpha: Spirocercidae) - Scholtz, Clarke H. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.